Biometry and Storage Ability at 4°C of Slaughtered Buck Testis and Correlations of Various Epididymal Seminal Attributes - Patel, Rajesh Pratap; Singh, Bhoopendra; Kumar, Rajesh; Srivastava, Sushant (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The present study was conducted on 48 pairs of fresh testicles obtained from mature bucks, irrespective of breed, slaughtered at local abattoir and AL-Nafees Proteins Pvt. Ltd., Mewat, Haryana. Various testicular and epididymal biometric parameters, epididymal seminal attributes and correlation coefficients between testicular volume and seminal epididymal attributes were studied. The testicles with epididymis were put randomly into six groups (plastic bags) each of eight pairs and were stored at 4°C for 96 hours in a refrigerator. One bag/group each was taken out at 6, 12, 24, 48, 72, and 96 hours of cold storage to study the effect of preservation at 4°C on the seminal epididymal attributes. The sperm concentration, total sperm output, progressive sperm motility, viability, HOS reactivity, and sperm with droplets decreased significantly (p <0.05) and progressively increased sperm head and tail abnormalities after 12 hrs of storage until 96 h. The testicular volume was significantly and positively correlated with sperm concentration (r = 0.76), total sperm output (r = 0.95), initial motility (r = 0.65), live sperm (r = 0.63), HOS reactive sperm (r = 0.66) and sperm with abnormal droplets (r = 0.60), however, it was negatively correlated with abnormal sperm head (r = -0.64) and sperm tail (r = -0.69).